FORMATION OF THE AIRLINE ALLIANCES - Krapko, Olena (Proceedings of National Aviation University (archive), 2016)
In the article we reviewed the necessity of combining forms, objectives of cooperation between airlines, studied the world's major aviation alliances, their composition and structure. We determined the main aspects of development aviation alliances. Researched the mechanism of forming alliances in aviation companies by dividing effects in the structure of alliances.